(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Digital transformation has driven Micro, Small, and Medium Enterprises (MSMEs) to adopt e-commerce-based strategies to enhance their competitiveness in the digital economy. This study aims to identify and analyze effective e-commerce strategies in strengthening the competitive position of MSMEs using a Systematic Literature Review (SLR) approach. The review was conducted on scholarly articles published between 2020 and 2025, following the PRISMA protocol and supported by tools such as Publish or Perish, Covidence, and VOSviewer. Analysis of 64 articles reveals that the use of marketplaces, social media, independent websites, and other digital technologies has significantly contributed to improving operational efficiency, market reach, and customer loyalty. However, the adoption of e-commerce still faces several challenges, including limited digital literacy, uneven infrastructure, and insufficient policy support. This study recommends collaborative efforts between governments, digital platforms, educational institutions, and MSME actors to build an inclusive and sustainable e-commerce ecosystem.